Frontispiece: Record Broken: A Copper Peroxide Complex with Enhanced Stability and Faster Hydroxylation Catalysis. Issue 50 (7th September 2017) - Liebhäuser, Patricia; Keisers, Kristina; Hoffmann, Alexander; Schnappinger, Thomas; Sommer, Isabella; Thoma, Anne; Wilfer, Claudia; Schoch, Roland; Stührenberg, Kai; Bauer, Matthias; Dürr, Maximilian; Ivanović‐Burmazović, Ivana; et al.
Abstract : Bis(pyrazolyl)methane copper peroxide complexes display tyrosinase‐like catalytic phenol hydroxylation activity. An exchange of the pyridinyl unit (background) by a methylimidazolyl unit (middle) enhances the catalytic activity. In turn, substituting the pyridinyl with a carboxymethyl group (foreground) enhances the stability and the catalytic activity in catalytic phenol hydroxylation. This makes the presented tyrosinase model the fastest catalytic model. Kinetic measurements reveal substrate‐binding behaviour and a biomimetic electrophilic reaction mechanism. DFT calculations show that the carboxymethyl substituent weakens the pyridinyl donor, which enhances the activity. For more details, see the Full Paper by S. Herres‐Pawlis et al. onpage 12171 ff.